PENGARUH LAMA BERMAIN VOLI TERHADAP KADAR ION KLORIDA (Cl-) DALAM DARAH PEMAIN VOLI STIKES NGUDIA HUSADA MADURA - SOLIHAH, RIYADATUS; R, RIZAL UMAR; HARIS, M SHOFWAN (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2021)
Sweat consist of both water and electrolytes, including chloride ion, so if the excretion of water and electrolyte is not corrected can disturb the body’s homeostasis and health. This study aimed to determine the different of chloride ion (Cl-) levels in the blood of volleyball players Ngudia Husada Madura STIKes between before and after playing volleyball 2 sets and 5 sets. This study was a pre –experimental with one group pretest-posttest, with two variables, namely the duration of playing volleyball and the levels of chloride ion (Cl-), the volleyball player population was 12 respondents. The sampling method was purposive sampling to obtain a total sample of 12 respondents blood sampling was performed before and after playing volleyball 2 sets and 5 sets for examination of chloride (Cl-) ion levels. The results showed that before playing volleyball the average value of chloride ion (Cl-) was 99,27 mEq/l, , after playing volleyball 2 sets and 5 sets in a row had an average value of chloride ion (Cl-) 99,58 mEq/l, and 99,72 mEq/l, . The statistical test results showed p = 0.04. It was concluded that there were significant differences in the levels of chloride ions(Cl-) When playing volleyball, there is a lot of sweat coming out, accompanied by some electrolyte fluid in the body so that it is necessary to pay attention to fluid and electrolyte intake from outside.